In silico and experimental approaches for validating RNA editing events in transcriptomes - Lai Wei (RNA Biology, 2024)
As a typical RNA virus, SARS-CoV-2 is subjected to RNA editing in host cells. While some researchers believe that a traditional variant calling pipeline retrieves all true-positive RNA editing events from the transcriptome, others argue that conventional methods identify many false-positive sites. Here, I describe several additional in silico and experimental approaches to validate the authenticity of RNA editing in SARS-CoV-2. These approaches include requiring strand-specific sequencing, analysis of hyperedited reads, linkage analysis, orthogonal methods like mass spectrometry, and the use of ADAR-deficient host cells. These findings may improve future analyses on the identification of RNA editing, especially in RNA viruses.